Empowerment Posyandu cadres in the transfer of spinach-based technology for early stunting prevention - Abdul Qodir; Dwi Soelistyoningsih; Wira Daramatasia; Ari Damayanti Wahyuningrum; Riza Rachmadhani; Sassilia Dwi Yulianti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The issue of nutritional health among toddlers has become a concern for the Indonesian government. The aim of this initiative is twofold: firstly, to prevent and early detect stunting in toddlers by leveraging local food resources through spinach-based technology, and secondly, to enhance the skills of Posyandu health cadres in spinach-based technology and improve their knowledge on stunting prevention. The service team will provide health education on stunting prevention using lecture and discussion methods and conduct anthropometric measurements. Practical or demonstration methods will be used to make cakes and jelly candies. The next stage is evaluation. Findings from the community empowerment evaluation show that health cadres are able to make jelly candy and spinach biscuits. The level of knowledge and skills of cadres on early stunting prevention and anthropometric measurements increased compared to before community empowerment. The evaluation results for knowledge and skill levels after training were 79.4 versus 66.5 before training. Paired t-test analysis found that the p-value was 0.002, so it was concluded that there was a significant increase in knowledge and skills scores in transferring spinach technology before and after training.